Excessive Daytime Sleepiness, but Not Insomnia Is Associated With Dyslipidaemia in Patients With Obstructive Sleep Apnoea Participating in ESADA - Bikov, Andras; Bailly, Sebastien; Anttalainen, Ulla; Saaresranta, Tarja; Basoglu, Ozen K.; Schiza, Sophia; Bouloukaki, Izolde; Sliwinski, Pawel; Pataka, Athanasia; Testelmans, Dries; Fanfulla, Francesco; Gouveris, Haralampos; et al. (Wiley-Blackwell, 2026)
Excessive daytime sleepiness (EDS) as well as insomnia have been associated with a higher risk for cardiovascular disease in patients with obstructive sleep apnoea (OSA). The link is not fully understood but may involve dyslipidaemia. The aim of the study was to analyse if the EDS and insomnia phenotypes were associated with deranged serum lipid values in patients with OSA recruited from a European real-world cohort. Patients with OSA and a full lipid profile participating in the ESADA database were analysed (n = 12,153). Based on their symptoms, they were categorised into EDS (n = 3123), EDS + insomnia (n = 2091), insomnia (n = 2862) and non-EDS non-insomnia (n = 4077) subgroups. Nonparametric ANCOVA adjusted for age, body mass index, smoking, alcohol, study site, apnoea-hypopnoea index and time spent with saturation below 90%, followed by Dunn's test and Bonferroni correction, was used to compare lipid values between the groups. The analyses were also performed in predefined subgroups. There were significant differences in total cholesterol (TC), LDL-cholesterol (LDL-C), HDL-cholesterol (HDL-C) and triglyceride (TG) values between the four groups (all p < 0.01). Patients with EDS had the highest TC (5.11 ± 1.08 vs. 5.00 ± 1.10, 5.03 ± 1.12, 5.04 ± 1.10 mmol/L, EDS vs. EDS + insomnia, insomnia, non-EDS non-insomnia, respectively), LDL-C (3.12 ± 0.97 vs. 3.01 ± 0.98, 3.02 ± 1.00, 3.09 ± 0.98 mmol/L) and TG (1.86 ± 1.04 vs. 1.76 ± 0.97, 1.69 ± 0.90, 1.75 ± 0.93 mmol/L) values and the lowest HDL-C results (1.18 ± 0.33 vs. 1.21 ± 0.34, 1.26 ± 0.38, 1.20 ± 0.34). Interestingly, patients with insomnia had the highest HDL-C values. EDS is significantly associated with dyslipidaemia in patients with OSA. Further studies are warranted to understand the link in detail and to translate it into clinical practice.